2016
DOI: 10.1007/978-1-4939-6469-7_10
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting Gibberellins Accumulation Sites in Arabidopsis thaliana Root Using Fluorescently Labeled Gibberellins

Abstract: The physical location of plant hormones is an important factor in maintaining their proper metabolism, perception, and mediated developmental responses. Thus, unveiling plant hormones dynamics at the molecule's level is essential for a comprehensive, detailed understanding of both their functions and the regulative mechanisms they are subjected to. Here, we describe the use of fluorescently labeled, bioactive gibberellins (GAs) to highlight the dynamic distribution and accumulation sites of bioactive GAs in Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…To elucidate the spatial distribution of GA, Shani et al [46] modified GA 3 /GA 4 by introducing a fluorescent moiety into its C6 position conjugated by amide linkage (GA 4 -Fl, 38; Figure 2(A)). Application of GA-Fl facilitates the visualization of GA dynamic distribution, such as its preferential localization to the root endodermis, ATP-dependent uptake, and accumulation regulated by ethylene (81, Figure 4(A)) through changes in GA transport [46,47]. Later research identified NPF3 to be a GA transporter by using GA-Fl [48].…”
Section: Auxinmentioning
confidence: 99%
“…To elucidate the spatial distribution of GA, Shani et al [46] modified GA 3 /GA 4 by introducing a fluorescent moiety into its C6 position conjugated by amide linkage (GA 4 -Fl, 38; Figure 2(A)). Application of GA-Fl facilitates the visualization of GA dynamic distribution, such as its preferential localization to the root endodermis, ATP-dependent uptake, and accumulation regulated by ethylene (81, Figure 4(A)) through changes in GA transport [46,47]. Later research identified NPF3 to be a GA transporter by using GA-Fl [48].…”
Section: Auxinmentioning
confidence: 99%